PEMANFAATAN TANAMAN KENCANA UNGU (RUELLIA TUBEROSA) SEBAGAI OBAT HERBAL DI DESA EHO HILISIMAETANO - Murniawati Daeli (Universitas Nias Raya, 2022)
This research is motivated by people who do not cultivate this purple golden plant (ruellia tuberosa) because it is only considered as an ornamental plant, when in fact this plant can actually provide good benefits, let alone used as herbal medicine. This study aims to determine the use of the purple golden plant as herbal medicine in Eho Hilisimaetano Village, Maniamolo District and to determine the perception of the people of Eho Hilisimaetano Village about the use of purple golden plant as herbal medicine. This research is a type of qualitative research with the number of informants as many as 4 (four) people. The source of data in this study is observations at the research site. The technique of collecting data is by using interview and documentation techniques. The data analysis technique used a method consisting of three stages, namely reduction, data modeling, and drawing conclusions. The results in this study are the use of the purple golden plant as a herbal medicine has several benefits, namely reducing kidney inflammation, relieving cough disease, treating injured skin, relieving hypertension, treating ulcer disease, relieving skin allergies. The conclusion in this study there are 3 ways to mix, namely by pounding, boiling, and drying. Suggestions in this research is to hope that this research can be useful for students, as a reference or comparison in conducting further research.